In Students In The Process of Literacy Teaching Formation of Spell Literacy - Adizova Nigora Bakhtiyorovna; Husenova Dilshoda (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2021)
In this article, literacy classes introduce students to sound and letters, teach them to read, as well as prepare the ground for literacy, spelling knowledge to improve students' speech, vocabulary at the expense of new words. It is emphasized that enrichment, the use of words in different grammatical forms, their formation at the same time as working on their pronunciation.